2010
DOI: 10.1140/epje/i2010-10608-1
|View full text |Cite
|
Sign up to set email alerts
|

Force networks and elasticity in granular silos

Abstract: We have made experimental observations of the force networks within a two-dimensional granular silo similar to the classical system of Janssen. Models like that of Janssen predict that pressure within a silo saturates with depth as the result of vertical forces being redirected to the walls of the silo where they can then be carried by friction. We use photoelastic particles to obtain information not available in previous silo experiments --the internal force structure. We directly compare various predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…Janssen's saturated stress profile may not be found before the discharge when the system is in a state of undetermined mobilization of friction, but may be produced by fully mobilizing the friction during the preparation of the system or by allowing it to evolve during the discharge. Previously, Wambaugh et al [14] studied the force chains inside a two dimensional silo controlling the initial mobilization and showed that when mobilization at the wall is not uniform, Janssen's screening effect is not produced. From these results regarding the stresses in the silo, even though these where obtained under experimental conditions different from ours, we arrive at the conclusion that in the cases under study in this paper the collapse is triggered by forces on the wall that may not produce a saturating stress profile as would be expected from the classical Janssen model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Janssen's saturated stress profile may not be found before the discharge when the system is in a state of undetermined mobilization of friction, but may be produced by fully mobilizing the friction during the preparation of the system or by allowing it to evolve during the discharge. Previously, Wambaugh et al [14] studied the force chains inside a two dimensional silo controlling the initial mobilization and showed that when mobilization at the wall is not uniform, Janssen's screening effect is not produced. From these results regarding the stresses in the silo, even though these where obtained under experimental conditions different from ours, we arrive at the conclusion that in the cases under study in this paper the collapse is triggered by forces on the wall that may not produce a saturating stress profile as would be expected from the classical Janssen model.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to monitor the movement of individual grains we use a software, developed using Python package SciPy, that identifies the position of individual grains through each frame of the video using a centroid technique. The image processing is very similar to the one used by Choi et al [8] and Wambaugh et al [18]. We use the observed fluctuations in the position of the grains before the discharge to estimate the uncertainty in their position after the discharge starts (±0.03d).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct consequence of this is the strong local heterogeneity of the stress distribution within the medium [7]. Since Dantu [8] and De Josselin de Jong [9], we already know that the distribution of the contact forces, resulting from an externally applied load, is very inhomogeneous [10,11], as shown in experiments by photoelastic visualization [9,11,12] and via simulations [10,13]. The contact network determines most salient mechanical properties of a dense granular medium such as its ability to bear load, its nonlinear elastic response, and flow behavior.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this discrepancy the Eurocode (EN 1991(EN -4, 2006 recommends using the overpressure factors to raise Janssen pressures to real experimental values. For small depths the profile of wall pressure is nearly linear (Wambaugh et al, 2010) and therefore some design standards (ANSI/ASAE EP446.3, 2013; ANSI/ASAE EP545, 2015) recommend calculating pressures in a shallow silo as the hydrostatic pressure for storage and flowing conditions. Janssen (1895) assumed that the vertical pressure across the radius of the bin is uniform.…”
Section: Introductionmentioning
confidence: 99%